The Methods of Change of Organizational Culture in Companies Using Lean Management - Piotr WALENTYNOWICZ; Jarosław SZREDER (Communications of International Proceedings, 2022)
Scientists and practitioners have recently emphasized the fact that in order to use Lean Management successfully, it is necessary to develop an appropriate organizational culture. In other words, changing the current culture to a lean-friendly organizational culture. Recently, many studies have been published on the features of Lean-friendly organizational culture. Likewise, there are many studies on how to change the culture in an organization. However, there is less research and studies dealing strictly with how to shape organizational culture as part of the implementation / application of Lean Management. This study aims to fill this gap from the theoretical and practical side. The first part of the article presents theoretical considerations on how to change the organizational culture in Lean Management. The second part presents the results of empirical research conducted in 2022 on the organizational cultures occurring in companies using Lean Management in Poland and the ways of shaping these cultures. In the authors' opinion, the results of these studies quite well reflect the state of the studied phenomenon in Poland and may constitute a comparative basis for research on this issue in other countries.
Keywords: Lean Management; organizational culture; change of organizational culture; results of empirical research